Review of Mark Twain's Letters, 1853–1880 of the Mark Twain Project Online - Hanrahan, Elise (Enthalten in:RIDE;Köln : Institut für Dokumentologie und Editorik, [2014]-;Online-Ressource)
Abstract: The Mark Twain Project Online (MTPO) provides digital critical editions of Mark Twain’s writings for the purpose of scholarly study. The edition project creates a foundation for in-depth research on Mark Twain’s person and texts, as well as contributes greatly to this research itself. All the editions and resources from the MTPO are available free of cost and without registration. The goal of the edition is to publish all of Mark Twain’s writings and this review concentrates particularly on their digital edition of Mark Twain’s letters. This edition project achieves a great deal of transparency regarding editorial principles and practices, making it easy for the reader to follow the editorial decisions. The amount of scholarly work put into the editing and commentary is commendable and offers a vast amount of information for research and analysis. The technical aspects of the digital edition are satisfactory, providing for a digital edition that is easy to read and use, however ...
10.18716/ride.a.10.2
Keywords: 19th century; critical edition; hybrid edition; letters; literature; modern; TEI